Aspects of legal communitarianism in Greece: between Millet and citizenship - Tsitselikēs, Kōnstantinos (Oñati Socio-Legal Series, 2012)
Legal and political percepts pertaining to ethnic belonging in Greece are closely linked to the ideological understanding of Greekness, a legacy of the Ottoman Greek-Orthodox millet system. Complementary to this image of the national self, minority protection law on Muslims and Jews was and still is partially formed through millet-like paradigms. Greece’s territorial expansion made all inhabitants of the annexed provinces Greek citizens en masse: in addition to those that were deemed eligible to belong to the Greek nation, Jewish and Muslim communities also acquired Greek citizenship. For these communities the self-autonomy of the Ottoman millet structure in education and religious matters was transformed into minority protection, through special rights (community schools, Moufti’s jurisdiction, Muslim foundations, military conscription) attributable through religion to citizens of the state.